2023
DOI: 10.3389/fimmu.2023.1265963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate on growth performance, antioxidant status, inflammatory response and resistance to hypoxic stress in juvenile largemouth bass (Micropterus salmoides)

Dongqiang Hou,
Min Li,
Peijia Li
et al.

Abstract: The aim of this study was to investigate the effects of sodium butyrate (SB) supplementation on growth performance, antioxidant enzyme activities, inflammatory factors, and hypoxic stress in largemouth bass (Micropterus salmoides). Diets were supplemented with different doses of SB at 0 (SB0), 0.5 (SB1), 1.0 (SB2) and 2.0 (SB3) g/kg. The hypoxic stress experiment was performed after 56 days of culture. The results showed that compared with the SB0 group, the final body weight, weight gain rate and protein depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…By 2022, annual largemouth bass production in China had soared to 0.8 million tons, marking a 14.3% increase from 2021. Nevertheless, the persistent threat of bacterial diseases has impeded the largemouth bass industry's progress [10]. Amidst efforts to reduce antibiotic usage and explore substitutes, the application of B. velezensis, renowned for its broad-spectrum antibacterial properties, brings renewed optimism to the largemouth bass industry.…”
Section: Discussionmentioning
confidence: 99%
“…By 2022, annual largemouth bass production in China had soared to 0.8 million tons, marking a 14.3% increase from 2021. Nevertheless, the persistent threat of bacterial diseases has impeded the largemouth bass industry's progress [10]. Amidst efforts to reduce antibiotic usage and explore substitutes, the application of B. velezensis, renowned for its broad-spectrum antibacterial properties, brings renewed optimism to the largemouth bass industry.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate levels (9% and 18%) and feed formulations were derived from our previous studies [ 33 ]. The added levels of SA and SB were based on previous studies where 2 g/kg of SA and SB were effective in improving liver and intestinal health in fish (Additional file 1: Table S 1 ) [ 23 27 , 34 ]. According to the principle of step-by-step enlargement, all feed ingredients were thoroughly mixed by hand, and soybean oil and distilled water were added sequentially.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, juvenile largemouth bass (Micropterus salmonids) fed with sodium butyrate (0, 0.5, 1, and 2 g/kg) demonstrated an increased antioxidant capacity and decreased immune function [15]. On the other hand, Liu et al (2014) [16] showed an increased immune response in common carp fed with sodium (0, 1.5, 3%).…”
Section: Introductionmentioning
confidence: 99%